Kahan Peningkatan Angkutan Pemadu Moda Di Bandara Samratulangi Manado - Lestari, Sri; Libania, Ratih (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Manado as one of the many tourist ta11m 11isited ln; domestic and foreign tourists are in need ofsupport infrastructure and transportntion facilities are inadequate both in qun.lihj and quantih;. Transportationneeds to be organized in a syst.ern of integmt.ed smrices in order to improve senrices to usersof transport sentices, at Airport Mnnndo Sam dotplwtogmplry inter-modnl integration has not beenperforming 1rell so that utilization is still low modal transportation allotjng. Kejian This qualitativedescriptiz;e method ln; using priman; data and secondan; data. The results slunred the cause of thelow utility in the airport transport multimoda Sam dotplwtograpln; is because there is no agreement(MOU) between the Department of Transportation of the cih; of Manado with manager Sam RatulangiAirport just a good relationship between the Department of Transportation 11rith Pt (Persero) LAP. IManado, not yet integrated aircraft and schedules between hus Trans Kmmnun and based on publicperception antannodn facilities at Sam Rnhtlangi Airport of Mnnado is not good enough, this isbecause based on respondents' perception distance passenger exits the bus shelter Trans Kawanuastill far and is still quite difficult to get a bus Trans Kmvanua at the Airport and the respondentsagreed that if there is integration beni:een the aircraft ln; bus Trans Kmvanua.Keywords: Feeder Mode